Impact of income shocks on asset portfolio of rural Indian households: An empirical analysis - Hemant Sharma (IBSU Scientific Journal (IBSUSJ), 2010)
People who live in low income economies often have to cope, not only with severe poverty, but also with extremely variable income. The high prevalence of risk in low economies implies that people's ability to manage uncertainty is critical for both productivity and their mere survival. This paper examines the effects of income shocks on the saving decision of rural households i.e. how an unpredictable peculiar income shock affects the composition of asset portfolio of rural households. A sincere attempt is made to gauge the effects of unanticipated health and weather related income shocks on the saving decision of a rural household. This study uses an Ordinary Least Squares Regression to analyze the saving behavior of households in response to health and weather shocks. The significant finding of this study is that the volatility of income adds to poverty of rural households by forcing them to reduce liquid assets. Results show that income shocks related to health are more significant to lead them to this than weather related income shocks. In view of the diversity of the structure of rural Indian households (like joint, nuclear and stem house holds.); impact of income shocks has been studied for all categories of rural households. It reveals significant differences in savings behavior between nuclear and joint households. Since, the study has found very strong link between health and income (for low income level), poor are more susceptible to an unpredictable health shock. Hence, the policy implication of the present paper is that the income of rural households can be raised considerably if government tends to design and introduce the appropriate micro health insurance schemes keeping in view the different behavior of joint and nuclear households.
Keywords: 330; asset portfolio; rural households; income volatility; health and weather shocks; household structure; India